Imunização genital de bezerras com uma cepa recombinante do herpesvírus bovino tipo 1 defectiva na glicoproteína E - Weiss, Marcelo (2009)
We herein report an evaluation of the attenuation and protection conferred by genital vaccination of heifers with a bovine herpesvirus type 1 strain (BoHV-1) defective in the glycoprotein E (SV265gE-). A group of six seronegative heifers was vaccinated with SV265gE- in the submucosa of the vulva (group IV; 106.9TCID50); four heifers were vaccinated intramuscularly (group IM; 107.6TCID50) and four heifers remained as nonvaccinated controls. Heifers vaccinated IV developed mild and transient local edema and hyperemia and shed low amounts of virus for a few days after vaccination, yet a sentinel heifer maintained in close contact did not seroconvert. Attempts to reactivate the vaccine virus in two IV vaccinated heifers by intravenous administration of dexamethasone (0.5 mg.kg-1) at day 65 post-vaccination (pv) failed since no virus shedding, recrudescence of genital signs or seroconversion were observed. At day 65 pv, all vaccinated and control heifers were challenged by genital inoculation of a highly virulent BoHV-1.2 isolate (SV-56/90, 107.4TCID50/animal). After challenge, virus shedding was detected in genital secretions of control animals for 8.2 days (8 9 days); in the IM group for 6.2 days (5 8 days) and during 5.2 days (5 6 days) in the IV group. Control non-vaccinated heifers developed moderate (2/4) or severe (2/4) vulvovaginitis lasting 9 to 14 days ( 11.2 days). The disease was characterized by vulvar edema, vulvovestibular congestion, small vesicles progressing to coalescence and erosions, fibrinonecrotic plaques and fibrinopurulent exsudate. IM vaccinated heifers developed mild (1/3) or moderate (3/4) genital lesions, lasting 10 to 13 days ( 11.5 days); and IV vaccinated heifers developed mild and transient (3/4) or mild to moderate genital signs (1/4), lasting 4 to 8 days ( 5.5 days). Clinical examination of the animals after challenge revealed that vaccination by both routes conferred some degree of protection, yet IV vaccination was clearly more effective in reducing the duration of virus shedding, the severity and duration of clinical disease. Taken together, these results demonstrate that SV265gE- is sufficiently attenuated upon IV vaccination in a low-titer dosis, is not reactivated after corticosteroid treatment and lastly, and more importantly, confers local protection upon challenge with a high titer of a virulent heterologous BoHV-1 isolate. Thus, this immunization strategy may be considered for the prevention of BoHV-1-associated genital disease in the field.